A Rapid Realist Review of Group Psychological First Aid for Humanitarian Workers and Volunteers - Corey, Julia (My University, 2021)
Humanitarian workers are at an elevated risk of occupational trauma exposure and its associated psychological consequences, and experience increased levels of anxiety, depression, and post-traumatic stress disorder (PTSD) compared to the general population. Psychological first aid (PFA) aims to prevent acute distress reactions from developing into long-term distress by instilling feelings of safety, calmness, self- and community efficacy, connectedness and hope. Group PFA (GPFA) delivers PFA in a group or team setting. This research sought to understand ‘What works, for whom, in what context, and why for group psychological first aid for humanitarian workers, including volunteers?’ A rapid realist review (RRR) was conducted. Initial theories were generated to answer the question and were subsequently refined based on 15 documents identified through a systematic search of databases and grey literature, in addition to the inputs from a core reference panel and two external experts in GPFA. The findings generated seven programme theories that addressed the research question and offered consideration for the implementation of GPFA for the humanitarian workforce across contexts and age groups. GPFA enables individuals to understand their natural reactions, develop adaptive coping strategies, and build social connections that promote a sense of belonging and security. The integrated design of GPFA ensures that individuals are linked to additional supports and have their basic needs addressed. While the evidence is sparce on GPFA, its ability to provide support to humanitarian workers is promising.
PUBLISHED
Keywords: Group psychological first aid; Psychological first aid; Humanitarian workers; Psychosocial support; International Development; EMERGENCIES; Global Mental Health